Femtosecond photodichroism studies of isolated photosystem II reaction centers. - Wiederrecht, G P (1994)
Photosynthetic conversion of light energy into chemical potential begins in reaction center protein complexes, where rapid charge separation occurs with nearly unit quantum efficiency. Primary charge separation was studied in isolated photosystem II reaction centers from spinach containing 6 chlorophyll a, 2 pheophytin a (Pheo), 1 cytochrome b559, and 2 beta-carotene molecules. Time-resolved pump-probe kinetic spectroscopy was carried out with 105-fs time resolution and with the pump laser polarized parallel, perpendicular, and at the magic angle (54.7 degrees) relative to the polarized probe beam. The time evolution of the transient absorption changes due to the formation of the oxidized primary electron donor P680+ and the reduced primary electron acceptor Pheo- were measured at 820 nm and 545 nm, respectively. In addition, kinetics were obtained at 680 nm, the wavelength ascribed to the Qy transition of the primary electron donor P680 in the reaction center. At each measured probe wavelength the kinetics of the transient absorption changes can be fit to two major kinetic components. The relative amplitudes of these components are strongly dependent on the polarization of the pump beam relative to that of the probe. At the magic angle, where no photoselection occurs, the amplitude of the 3-ps component, which is indicative of the charge separation, dominates. When the primary electron acceptor Pheo is reduced prior to P680 excitation, the 3-ps component is eliminated.